An investigation of construction professionals’ perceptions of construction managers’ soft skills in complex construction projects in South Africa - Sekhu, Madimetja Solomon (My University, 2019)
Purpose: The purpose of this study was to investigate construction professionals’ perceptions of construction managers’ soft skills in complex construction projects in South Africa. Design/methodology: The survey and interviews were conducted in Gauteng Province (South Africa), which is the economic hub of the country. The study used a concurrent triangulation (mixed method) approach, where both quantitative and qualitative approaches were applied. The questionnaires were based on a list of 23 soft skills and training strategies extracted from previous research papers. The instruments for data collection were survey questionnaires and interviews. Findings: Statistical Package for Social Science Software (SPSS) version 25 was used to perform descriptive statistics, mean, standard deviation, and Relative Importance Indices (RII). The findings reveal 15 soft skills that are very important, with mean scores of between 4 and 4.63; and eight important soft skills, with mean scores of between 3 and 95. The overall results indicate that communications skills are considered very important, with a mean score of 4.63. Research limitation: The sample was drawn from a limited number of respondents from construction professionals based in Gauteng Province (South Africa). It would therefore not be appropriate to generalise the effects of the study to other provinces without considering their unique skills in managing complex projects. Practical implications: Understanding project complexity and its contributing factors helps construction professionals and construction managers to understand the challenges, dynamics, and complex nature of the construction industry. This highlights the importance of construction managers’ proficiency in soft skills. Originality/Value: This study proposes a list of soft skills and training needs, and their importance for construction managers in complex projects. The study also emphasises the importance of the ability of construction managers’ soft skills in complex projects. Therefore, construction organisations would be encouraged to look beyond traditional skills-based training.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, February 2019
Keywords: Construction industry--Management; Construction industry; Building--Estimates--South Africa